Research status of visuospatial dysfunction and spatial navigation - Bao, Rui; Chang, Shijie; Liu, Ruixiang; Wang, Yunning; Guan, Yifu (Frontiers in Aging Neuroscience, 2025)
Visuospatial function is a critical aspect of cognitive abilities, encompassing visual perception, attention, memory, and adaptive responses to spatial changes. This paper reviews studies on human visuospatial function, spatial navigation, and factors contributing to visuospatial impairments. After introducing fundamental concepts of visuospatial function and spatial navigation, classical methods for assessing visuospatial performance are summarized. By examining recent advances in spatial navigation studies, this paper discusses factors influencing spatial navigation capabilities and explores how spatial navigation paradigms can be used to investigate visuospatial cognitive impairments. Finally, current limitations in spatial navigation research are highlighted. Overall, the current research has not yet reached definitive conclusions regarding visuospatial aspects. However, this paper aims to enhance the understanding of visuospatial dysfunction and spatial navigation, providing valuable references for future research.